Dotyk detalu: Katherine Mansfield, "Opowiadania", wybrała, przełożyła i posłowiem opatrzyła Magda Heydel, Wydawnictwo Officyna, Łódź 2020 - Sobczak, Izabela (Zagadnienia Rodzajów Literackich, 2024)
The article serves as a critical commentary on the new award-winning Polish translation of Katherine Mansfield’s stories Opowiadania (2020) by Magda Heydel. The aim of the text is to look at Heydel’s translation strategy against the background of the modernist historical context and to see how the translation reflects the feminist charge that is revealed both in the interpretation of the particular stories and in the internal orientation that binds the various titles together and constitutes the collection. This will shed light on the change that the new translation provides in reception of Mansfield in Poland, which had been rather tendentiously fashioned for decades, since the first appearance of her work on the Polish market in 1910. In my analysis, I focus on Mansfield’s metonymic writing style, which not only indicates affiliations with modernist narrative strategies (Gaston Bachelard), but also highlights the detail that serves as a textual but tangible signal of woman’s relationship with others and with herself. Mansfield’s perspectival focus on detail and narrative technique based on equivalents and ellipses draws attention to the “interstices” of the text, between which an intimate experience emerges. This aspect, I believe, points to the way in which Heydel’s translation supports Manfield’s authorial independence, revaluates, and revitalizes her work in Poland and situates it within the contemporary philosophical thought represented by Jolanta Brach-Czaina.